Post stroke aspiration pneumonia, associated factors, and treatment outcome among stroke patients admitted to Tibebe Ghion Specialized Hospital, Bahir Dar, Ethiopia - Nigus, Molla Dessalegn; Sendek, Ergoye Melese; Ewunetu, Mulugeta Biyadgie; Cherkos, Abel Belete; Yimer, Awol Arega (Frontiers in Stroke, 2024)
Background: Post-stroke aspiration pneumonia is a serious lung infection that occurs when stroke patients inhale food, saliva, liquid, vomit, or foreign objects. It is the leading cause of death for stroke patients worldwide, which accounts for 60% of stroke-associated deaths. Little is known about its prevalence, adverse outcomes, and determinants in Ethiopia. Therefore, this study aims to evaluate the prevalence of post-stroke aspiration pneumonia and associated factors in stroke patients admitted to the Tibebe Ghion Specialized Hospital.A retrospective cross-sectional study was conducted on 242 stroke patients admitted to the neurology unit of a medical ward from January 1, 2019, to December 30, 2020. Data were collected from the patients' cards using a pre-developed data collection tool. The collected data was coded, cleaned, and entered into Epi-Info version 7.25, and then exported to SPSS 26 for further analysis. Logistic regression analyses were performed to identify factors associated with aspiration pneumonia. The adjusted odds ratio with the corresponding 95% confidence interval and a p-value less than 0.05 were noted to declare variables had a significant association.The mean age of the patient was 61.15±13.959 years with a minimum age of 21 and maximum age of 102 years. Males account for 55.8% and females for 44.2%. Out of 242 patients post-stroke aspiration pneumonia was identified in 23.1% of patients, and 55.4% of stroke patients improved, while 23.2% died from post-stroke aspiration pneumonia. The study found that having